THE IDEA OF HISTORICAL CIRCULUS IN THE NOVEL THE BRIDGE ON THE DRINA BY IVO ANDRIC - Mirna Brkić Vučina (Hum, 2012)
It is necessary to start the speculations on history and its repetition in the novels of Croatian literature with Senoa and the concept of history developed in his historical novels. For Senoa, history is magistra vitae, the teacher of life, which expresses his attitude that, based on the acquired experiences, you can avoid mistakes and find better solutions. However, the genre of historical novel in Croatian literature has been constantly changing, as well as the concept of history within it and the affirmative attitude towards the past has been replaced by the vision of history as the time of evil, madness and death. Such a negative attitude towards history will be depicted in this paper through the example of novel The Bridge on the Drina (1945) by Ivo Andric.The main idea of historical circulus, i.e. recognition of the present through the past and vice versa and their permanent turns, has marked this mentioned novel.